The effect of credit risk, liquidity risk and capital adequacy on bank performance / Faridatul Fazwin Abd Rahim - Abd Rahim, Faridatul Fazwin Abd Rahim (2019)
This paper is come out to determine the effect of credit risk and liquidity risk on banks performance based on top 5 commercial banks in Malaysia as stated by Corporate Finance Institute. This study was conducted on a period from 2009 until 2018. Many previous researcher come out with different results, some say have a positive and significant and some researchers found negative and significant. The method on this study is multiple linear regression in order to test the relationship between dependent variable (ROE) and independent variables (credit risk, liquidity risk and capital adequacy ratio). To conclude, credit risk and liquidity risk have positive and significant relationship with ROE while capital adequacy ratio have negative and significant relationship with ROE.